Comparative and functional analysis of plasma membrane-derived extracellular vesicles from obese vs. nonobese women. Issue 4 (April 2020) - Santamaria-Martos, Fernando; Benitez, Iván D.; Latorre, Jèssica; Lluch, Aina; Moreno-Navarrete, José M.; Sabater, Mònica; Ricart, Wifredo; Sanchez de la Torre, Manuel; Mora, Silvia; Fernández-Real, José M.; Ortega, Francisco J.
Summary: Background: Membrane-derived extracellular vesicles (EVs) are released to the circulation by cells found in adipose tissue, transferring microRNAs (miRNAs) that may mediate the adaptive response of recipient cells. This study investigated plasma EVs from obese vs. nonobese women and their functional impact in adipocytes. Methods: Plasma EVs were isolated by differential centrifugation. Concentration and size were examined by nanoparticle tracking analysis (NanoSight). RNA was purified from plasma and plasma EVs of 45 women (47 ± 12 years, 58% of obesity) and profiles of mature miRNAs were assessed. Functional analyses were performed in human adipocytes. Findings: Smaller plasma EVs were found in obese when compared to nonobese women. Positive associations were identified between circulating EVs numbers and parameters of impaired glucose tolerance. Almost 40% of plasma cell-free miRNAs were also found in isolated plasma EVs, defined as Ct values < 37 in ≥75% of samples. BMI together with parameters of insulin resistance were major contributors to EVs-contained miRNA patterns. Treatments of cultured human adipocytes with EVs from obese women led to a significant reduction of genes involved in lipid biosynthesis, while increasing the expression of IRS1 (12.3%, p = 0.002). Interpretation: Size, concentration and the miRNA cargo of plasma EVs are associated with obesity and parameters of insulin resistance. Plasma EVs may mediate intercellular communication relevant to metabolism in adipocytes.